Metformin inhibits cell proliferation in SKM-1 cells via AMPK-mediated cell cycle arrest - Xiaojia Zhou; Yunchun Kuang; Simin Liang; Li Wang (Elsevier, 2019)
Metformin, a widely used antidiabetic drug, has previously been demonstrated to exert anti-cancer effects in certain hematological malignancies, but its effects on the transformation of myelodysplastic syndromes to acute myeloid leukemia (AML-MDS) remain unclear. The present study aimed to investigate the effects of metformin on SKM-1 cells (an AML-MDS cell line) and its underlying mechanisms. SKM-1 cells were treated with different concentrations of metformin. Cell proliferation was assayed by CCK-8. Apoptosis and cell cycle phases were detected by flow cytometry, while cell cycle related proteins and AMPK were tested by Western blot. SKM-1 cells were transfected with LV-AMPKα1-RNAi to reduce the expression of AMPK. Metformin inhibited cell proliferation in a dose and time dependent manner by inducing G0/G1 phase arrest rather than apoptosis induction. Metformin promoted the expression of p-AMPK, P53, P21CIP1 and P27KIP1, while inhibited the expression of CDK4 and CyclinD1. AMPK knockdown attenuated the effects of metformin on SKM-1 cells. These findings suggested that metformin inhibited proliferation of SKM-1 cells, potentially through an AMPK-mediated cell cycle arrest. Keywords: SKM-1 cells, Metformin, AMPK, Cell cycle